2021
DOI: 10.3390/su13169336
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Added Cementitious Materials—A Review on Mechanical, Thermal, and Environmental Properties

Abstract: The enhanced carbon footprint of the construction sector has created the need for CO2 emission control and mitigation. CO2 emissions in the construction sector are influenced by a variety of factors, including raw material preparation, cement production, and, most notably, the construction process. Thus, using biobased constituents in cement could reduce CO2 emissions. However, biobased constituents can degrade and have a negative impact on cement performance. Recently, carbonised biomass known as biochar has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 127 publications
(147 reference statements)
0
13
0
Order By: Relevance
“…Biochar emerges as a carbon negative source that has been incorporated in suitable proportions with the cement for construction purpose and acts as a partial replacement of cement. It is reported that biochar enhances the mechanical strength and thermal properties of the concrete, thereby reducing the CO2 emissions (Mensah et al, 2021).…”
Section: Ghgs Emissions Reduction and Neutral Carbon Footprintmentioning
confidence: 99%
“…Biochar emerges as a carbon negative source that has been incorporated in suitable proportions with the cement for construction purpose and acts as a partial replacement of cement. It is reported that biochar enhances the mechanical strength and thermal properties of the concrete, thereby reducing the CO2 emissions (Mensah et al, 2021).…”
Section: Ghgs Emissions Reduction and Neutral Carbon Footprintmentioning
confidence: 99%
“…In this sense, the feasibility of utilizing bio-waste as a potential filler material for cement was also considered: different amounts of eggshell powder (0, 5%, 10% and 15% by weight) were adopted to replace cement, and the authors found that calcium carbonate in the biowaste can react with the aluminium phase in the cement to produce monocarboaluminate; they also concluded that the replacement level of 5% provides the best performance and reduces environmental pollution. 228,229 Biowaste can also be thermally converted into char by pyrolysis treatment and subsequently introduced into cementitious matrix-forming cement-based composites (Fig. 12).…”
Section: Biowaste Feedstocks For Nanofillersmentioning
confidence: 99%
“…According to this data, the global biocomposites industry is expected to have a large market. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to this data, the global biocomposites industry is expected to have a large market. [7,8] Natural fiber, which is derived from plants or animals, is the best reinforcing material for biocomposites. The fibers such as bamboo, coir, hemp, jute, banana, flax, kenaf, sisal, pineapple leaf, and ramie extracted from various parts of the plants can be used in bio-polymer as reinforcing materials.…”
mentioning
confidence: 99%